The influence of heart failure on the pharmacokinetics of cardiovascular and non‐cardiovascular drugs: a critical appraisal of the evidence. Issue 1 (14th October 2018) - Mangoni, Arduino A.; Jarmuzewska, Elzbieta A.
Abstract: Prescribing in heart failure (HF), a common disease state that predominantly affects the older population, is often a challenging task because of the dynamic nature of the condition, requiring frequent monitoring and medication review, the presence of various comorbidities, and the frailty phenotype of many patients. The significant alterations in various organs and tissues occurring in HF, particularly the reduced cardiac output with peripheral hypoperfusion and the structural and functional changes of the gastrointestinal tract, liver and kidney, might affect the pharmacokinetics of several drugs. This review critically appraises the results of published studies investigating the pharmacokinetics of currently marketed cardiovascular and selected non‐cardiovascular drugs in HF patients and control groups, identifies gaps in the current knowledge, and suggests avenues for future research in this complex patient population.